PROSES PENANAMANSIKAP NASIONALISME DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL PADA SISWA KELAS TINGGI SD TAMAN MUDA IBU PAWIYATAN YOGYAKARTA TAHUN AJARAN 2016/ 2017 - Meita Ratnasari; Kristi Wardani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
This research aim to describe the process of the nationalism attitude inculcation in the Social Science (IPS) learning in the high grade of Elementary School of Taman Muda Ibu Pawiyatan in an academic year 2016/ 2017 and describe some obstacles. This research is a descriptive qualitative study. The subjects of the research are the principal of the school as well as teachers and students of  high  grade  (IV,  V,  and  VI).  The  technique  are  collecting  data  using  interviews, observation, and documentation. The analysis of data using measures of data collection, data reduction, data presentation,  and  drawing  conclusions.  For  an  examination  of  the  validity  of  the  data  using triangulation sources, techniques, and time. The results of the research show that the way of the teachers to inculcate nationalism attitude through in the learning of IPS on the high grade students in Elementary School of Taman Muda Ibu Pawiyatan is by habituation, exemplary, provision of contextual examples, the use of stories, as well as the use of instructional media. The supporting factors of the inculcate of nationalism attitude include the teacher’s creativity in delivering learning materials of the IPS, availability of learning facilities, and their use of learning resources with outting activities or visits. The factors of inhibiting are the limited allocation of instructional time to learning materials of IPS and the limited of learning media. The ways that used to solve for the variety of inhibitor factors are to provide additional learning time and do the procurement of instructional media, and perform the learning activities in groups to minimize the amount of media use in the learning activities of IPS. The values  that can be developed in the realization of nationalism attitude for students in high grade in Elementary School Taman Muda Ibu Pawiyatan are willing to sacrifice, patriotism, uphold the good name of the Indonesian nation, proud as a citizen of Indonesia, unity and integrity, adherence to the rules, discipline, brave, honest, and hard working.